Parlamentarische Redefreiheit Eine rechtsvergleichende Untersuchung im Spannungsverhältnis von Status- und Grundrechten - Kemper, Thomas Johannes (Mohr Siebeck, 2024)
Debating culture in European parliaments has changed, with the use of insults and hate speech during plenary sittings having greatly increased. Thomas Johannes Kemper deals with the legal foundations and the limits of the MPs freedom of speech by comparing the situation in the German Bundestag, the French Assemblée Nationale, and the European Parliament.
PublicationDate: 20240708
Keywords: Meinungsfreiheit -- Freies Mandat -- Ordnungsgeld -- Sitzungsausschluss -- Würde des Parlaments -- Linking Rule -- Verfassungsrecht und Staatslehre -- Völkerrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung